Upshot of supply chain assimilation and competitive advantage on organizational performance in Ethiopia, Hawassa Industrial Park - Mintesnot Abay Mitiku; Fentahun Eylachew Nega (goodwood publishing, 2021)
Purpose: The aim of the investigation remained to observe the upshot of supply chain assimilation (SCA) and competitive advantage towards organizational recital in Ethiopian industrial Park corporation special reference of Hawassa Industry Park. Research methodology: To that end, the study adopted an explanatory research design with a mixed approach; and it utilizes a stratified sampling technique to select the relevant firms. In cooperation, first-hand and second-hand sources of data were accessed. Results: SCA has a considerable effect on both competitive advantage and Business recital and SCA has an indirect considerable upshot on Business recital over and done with a competitive advantage in the case firms’. Limitations: The study has been unable to see the upstream side of the firms from the perspective of their supplier since they are located abroad but from the firms’ perspective. Contribution: This study has a significant contribution to firms that are engaged in manufacturing, ministers of trade and investment, and future researchers.